Improving Teacher Organizational Citizenship Behavior (OCB) through Servant Leadership, Justice and Self-efficacy: Indonesian Teacher Perspective - Rais Hidayat; Yuyun Elizabeth Patras (Pedagonal : Jurnal Ilmiah Pendidikan, 2022)
The different roles of teacher behavior or organizational citizenship behavior (OCB) can be a lifesaver for schools. This study aims to find strategies to improve such behaviors. This study uses a quantitative approach with path analysis using SMART PLS. The population and sample of this study were 243 junior high school teachers in Bogor Regency, West Java, Indonesia. The main findings of this study are that improving teacher OCB will be faster and more effective if it is done with improved Servant leadership, self-efficacy, and organizational justice. Strategies to enhance teacher OCB are: strengthening forward-looking insights, committing to teacher progress, building community, increasing self-confidence, building a good perception of the strengths possessed, the virtues of the organization, love for the organization, and improving organizational integrity.